2022
DOI: 10.1039/d1cp04413c
|View full text |Cite
|
Sign up to set email alerts
|

Janus Ga2SeTe/In2SSe heterostructures: tunable electronic, optical, and photocatalytic properties

Abstract: Stacks of two dimensional materials vertically into van der Waals (vdW) heterostructures (HS) is deemed to be effective strategy to tailor their physical properties and enrich their applications in modern...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…This indicates that the observed bilayers were very active in the visible light range accounting for approximately 43% of the sunlight. Also, the absorption coefficients in the visible light region were comparable to other two-dimensional bilayers with similar structures like Ga 2 SeTe/In 2 SSe (∼10 5 cm −1 ); 60 Ga 2 STe/GaInS 2 (∼10 5 cm −1 ); 61 Ga 2 S 3 /Ga 2 SSe (∼10 4 cm −1 ). 29 As a result, Janus Ga 2 STe bilayers could be considered candidates for optoelectronic devices due to the effective utilization of sunlight.…”
Section: Resultssupporting
confidence: 76%
“…This indicates that the observed bilayers were very active in the visible light range accounting for approximately 43% of the sunlight. Also, the absorption coefficients in the visible light region were comparable to other two-dimensional bilayers with similar structures like Ga 2 SeTe/In 2 SSe (∼10 5 cm −1 ); 60 Ga 2 STe/GaInS 2 (∼10 5 cm −1 ); 61 Ga 2 S 3 /Ga 2 SSe (∼10 4 cm −1 ). 29 As a result, Janus Ga 2 STe bilayers could be considered candidates for optoelectronic devices due to the effective utilization of sunlight.…”
Section: Resultssupporting
confidence: 76%
“…26 Gong et al grew TMD heterostructures of size larger than 169 μm through a two-step chemical vapor deposition, and the strong photocurrent response and photovoltaic effect with a high quantum efficiency of the heterostructures have been detected. 27 In addition to vdW heterostructures based on 2D TMD, various 2D heterostructures have been reported with type II band alignment, such as heterostructure based on group-III monochalcogenides, 2,28,29 group-IV monochalcogenides, 30,31 and phosphorene. 32–34 Excellent power conversion efficiency (PCE) has been reported in InS/InSe 2 , Mo 2 SeTe/W 2 STe, 35 and phosphorene/MoS 2 34 heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Janus vdWHs have been widely studied and classified into three categories: Janus TMDs–TMDs, , Janus TMDs–graphene, , and heterostructures composed of Janus TMDs and other traditional 2D materials. Many studies have found that these Janus vdWHs exhibited promising potential in terms of electronic properties, photocatalytic properties, Rashba effect, and piezoelectric effect. For instance, Lin et al investigated the physical structure and optoelectronic properties of Janus Ga 2 SeTe/In 2 SSe heterostructures, and the materials have been found to be promising for applications in the visible and UV systems. Nguyen et al investigated the interfacial and optical properties of graphene/Ga 2 SSe vdWHs, demonstrating its potential for application in Schottky nanodevices.…”
Section: Introductionmentioning
confidence: 99%